2016
DOI: 10.1103/physrevlett.117.017001
|View full text |Cite
|
Sign up to set email alerts
|

Composite Topological Excitations in Ferromagnet-Superconductor Heterostructures

Abstract: We investigate the formation of a new type of composite topological excitation -the skyrmionvortex pair (SVP) -in hybrid systems consisting of coupled ferromagnetic and superconducting layers. Spin-orbit interaction in the superconductor mediates a magnetoelectric coupling between the vortex and the skyrmion, with a sign (attractive or repulsive) that depends on the topological indices of the constituents. We determine the conditions under which a bound SVP is formed, and characterize the range and depth of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 60 publications
2
45
1
Order By: Relevance
“…Similar expression has been obtained in Ref. 24 by a different approach, where Lorentz force due to currents applied into the superconductor was not considered. At this point, we call for attention to three different scenarios in Eq.…”
Section: Guiding Magnetic Skyrmions By Vortex-screened Hall Effectsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar expression has been obtained in Ref. 24 by a different approach, where Lorentz force due to currents applied into the superconductor was not considered. At this point, we call for attention to three different scenarios in Eq.…”
Section: Guiding Magnetic Skyrmions By Vortex-screened Hall Effectsupporting
confidence: 76%
“…Particularly, ferromagnetsuperconductor (FM-SC) heterostructures have received much attention in recent years [9][10][11][12] , either for their possible applications in spintronics 13 and Josephson devices [14][15][16][17] , or for the rich emergent physics in such systems [18][19][20][21][22] . Recently, theoretical works on chiral FM-SC heterostructures have demonstrated that the stray magnetic field of superconducting vortices may be able to create 23 magnetic skyrmions in the ferromagnetic layer, also to trap or repel the preexisting skyrmions 24,25 , depending on vortex polarity. First insights in the dynamic properties of such hybrid systems were recently provided in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A protection layer of 10 nm MgO is furthermore deposited between superconductor and ferromagnet to reduce pair-breaking effects. As previously reported, the interaction across the interface is dominated by magnetic dipolar coupling [18][19][20].…”
supporting
confidence: 68%
“…The superconducting order parameter is spatially dependent to account for the vortex, ∆(r) = e ibϕ ∆(r) with integer b and ∆(r) = ∆(1 − e −r/Rv ), where the vortex and the skyrmion cores are both located at the origin. This configuration can be energetically stable [54,67,68]. Then, the modified angular momentum operator…”
Section: Majorana Criterion In a Skyrmion-vortex Pairmentioning
confidence: 99%
“…47 in order to cirumvent the requirement of a DWS, by combining an SWS with a vortex in the superconductor. Such skyrmion-vortex pairs have been shown to be stable under suitable conditions [54]. MBS being bound to vortex cores is a concept that has been known for many years [55] for two-dimensional p-wave superconductors.…”
Section: Introductionmentioning
confidence: 99%